2014
DOI: 10.1021/ja4130803
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Gated Split-Kinases

Abstract: The activity of protein kinases are naturally gated by a variety of physiochemical inputs, such as phosphorylation, metal ions, and small molecules. In order to design protein kinases that can be gated by user-defined inputs, we describe a sequence dissimilarity based approach for identifying sites in protein kinases that accommodate 25-residue loop insertion while retaining catalytic activity. We further demonstrate that the successful loop insertion mutants provide guidance for the dissection of protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…This led to the facile identification of potential sites for fragmentation and CID dependent reassembly of splitkinases. 30 In our approach, the identification of sequences in the catalytic domain of protein kinases, particularly loops that harbor significant dissimilarities, guided the design of loop insertion mutants. We hypothesized and subsequently demonstrated that the catalytically active loop insertion mutants predicted sites for fragmentation of the parent enzyme to ultimately afford CID gated split-kinases.…”
Section: ■ Background Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to the facile identification of potential sites for fragmentation and CID dependent reassembly of splitkinases. 30 In our approach, the identification of sequences in the catalytic domain of protein kinases, particularly loops that harbor significant dissimilarities, guided the design of loop insertion mutants. We hypothesized and subsequently demonstrated that the catalytically active loop insertion mutants predicted sites for fragmentation of the parent enzyme to ultimately afford CID gated split-kinases.…”
Section: ■ Background Results and Discussionmentioning
confidence: 99%
“…For the construction of split phosphatases, N-terminal and C-terminal PCR products were cloned into the pRSFD-FKBP-linker-MCS and pRSFD-MCS-linker-FRB plasmids generated previously. 30 PYL cs /ABI cs * and GID1/ GAI(92) split kinases, pRSFD-PYL cs -linker-MCS, ABI cs *-linker-MCS, GID1-linker-MCS, and GAI(92)-linker-MCS plasmids were generated by cloning the respective PCR products with appropriate forward and reverse primers using BamHI/NotI sites into a pRSFDuet vector containing a 25 residue loop flanked by NotI and MfeI restriction sites. In a similar fashion, pRSFD-MCS-linker-PYL cs , pRSFD-MCS-linker-ABI cs *, pRSFD-MCS-linker-GID1, and pRSFD-MCS-linker-GAI plasmids were also generated by cloning the respective PCR products with appropriate forward and reverse primers using EcoRV/KpnI sites into a pRSFDuet vector containing a 27 residue loop flanked by NotI and MfeI restriction sites.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In attempts to develop a general fragment complementation system, Ghosh and coworkers designed kinases that could tolerate small loop insertions in their catalytic domain without compromising their catalytic activity (Camacho-Soto et al, 2014). Insertions were deliberately incorporated into regions of the catalytic domain of several tyrosine kinases (TKs) that shared little sequence homology, suggesting these regions were not essential for activity.…”
Section: Activation Of Pre-proteinsmentioning
confidence: 99%
“…[3] Engineering challenges include the high levels of dark (background) activity that inadvertently up- or down-regulate genes and biochemical pathways of interest. Several strategies have been described to address these issues, including protein sequestration and subsequent release, [4] the use of split protein constructs that are only active upon reconstitution, [5] and the application of nonsense suppression technology to introduce non-standard amino acids [6] . Each of these strategies offers elegant solutions to the construction of light-activated proteins.…”
mentioning
confidence: 99%